FROCOGERATOR (FREE FREON COOLER REFRIGERATOR) SEBAGAI INOVASI KULKAS PENYIMPAN BUAH DAN SAYURAN YANG RAMAH LINGKUNGAN BERBASIS TRANSFER KALOR ADSORBEN-ADSORBAT YANG LOW POWER - Pamungkas, Guntur M.; H., Halimah; Adam, Muhammad Fadli (Program Kreativitas Mahasiswa - Karsa Cipta, 2013)
In this activity, the team develop new technology for refrigerator without the use of freon base on absorbent and absorbat. This technology is expected to generate new breakthrough in electronic technology in Indonesia. This activity is expected to generate refrigerator without Freon that it has similar cooler quality, yet is more environmentally friendly and low electrical consumption. The team are able to produce a non-freon refrigerator prototype and it runs well.